AB0251 The Impact of Missing Anti-Citrullinated Protein Antibody (ACPA) Serology on Outcomes in Early Rheumatoid Arthritis: Results from Catch (Canadian Early Arthritis Cohort). (10th June 2014) - Shu, J.; Bykerk, V.; Boire, G.; Haraoui, B.; Hitchon, C.; Thorne, C.; Tin, D.; Keystone, E.; Pope, J.
Abstract : Background: Anti-citrullinated protein antibody (ACPA) is a serum biomarker that is as sensitive as, but more specific than the rheumatoid factor (RF) and detected earlier in RA [1, 2]. Although ACPAs are part of the ACR RA classification criteria, ACPA testing is not routinely paid for/accessible in all jurisdictions. Objectives: The impact of missing ACPA in early inflammatory arthritis patients was studied to determine if failure to perform ACPA testing could cause a gap in care. Methods: 2191 patients recruited to CATCH were allocated to 3 groups: 1. seropositive (rheumatoid factor positive (RF+) and/or ACPA+), 2. seronegative (RF−/ACPA−) and 3. missing ACPA (RF negative [RF−]). Adjustments were made using regression analyses for age, sex, symptom duration, and smoking status if p<0.1 from Pearson's Chi-squared or Analysis of variance (ANOVA) tests. Results: Refer to Table 1 for characteristics of three groups. More seropositive patients fulfilled 2010 ACR/EULAR RA criteria (Table 1 ). At 3 months, group 3 was treated with less DMARDs and methotrexate, but there were no significant differences in DAS28, HAQ-DI, corticosteroids, or physician/patient global assessments (Table 1 ). Conclusions: Patients with missing ACPAs were less likely to fulfill RA criteria and were treated differently with fewer medications. There may be a care gap in the unknown ACPA group who were RF negative, but there were no significant differences in outcomes such as DAS28, 3 month change in DAS28, or HAQ-DI despite less treatment. Further study is needed regarding the cost-effectiveness of ensuring ACPA testing is available for patients with new onset inflammatory arthritis. References: Whiting PF, Smidt N, Sterne JA, Harbord R, Burton A, Burke M, et al. Systematic review: accuracy of anti-citrullinated Peptide antibodies for diagnosing rheumatoid arthritis. Annals of internal medicine. 2010;152(7):456-64; W155-66. Rantapaa-Dahlqvist S, de Jong BA, Berglin E, Hallmans G, Wadell G, Stenlund H, et al. Antibodies against cyclic citrullinated peptide and IgA rheumatoid factor predict the development of rheumatoid arthritis. Arthritis and rheumatism. 2003;48(10):2741-9. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2635